On F-\(α\)-Geraghty Contractions - Janwised, Jiraporn; Kitkuan, Duangkamon; Bunpatcharacharoen, Pheerachate (Communications in Mathematics and Applications, 2018)
In this paper, we introduce the notion of F-\(α\)-Geraghty contraction type mappings and establish some common fixed point theorems for an admissible pair mappings under the notion of F-\(α\)-Geraghty contractive type in the setting of metric spaces. We give example for support results.